DEVELOPMENT OF GUIDED INQUIRY-BASED PHYSICS TEACHING MATERIALS TO INCREASE CRITICAL THINKING SKILLS OF HIGHSCHOOL STUDENTS - Nisa, E. K.; Jatmiko, B.; Koestiari, T. (Jurnal Pendidikan Fisika Indonesia, 2018)
This study aims to produce teaching materials based on inquiry physics to improve the critical thinking skills of high school students. This type of research is Research and Development and refers to the 4-D development model. This study was tested in class X. The results of this study obtained some findings include: 1) the validation of teaching materials obtained categories are very valid and reliable; 2) test legibility of physics teaching materials categorized high readability; and 3) N-gain improves students' critical thinking skills. Based on the results of this research, it can be concluded that the guided inquiry-based physics teaching materials worthy of use in learning and can improve the critical thinking skills of high school students.